Leishmania infantum Induces the Release of sTREM-1 in Visceral Leishmaniasis - Bomfim, Lays G. S.; Magalhães, Lucas S.; Santos-Filho, Marcello A. A.; Peres, Nalu T. A.; Corrêa, Cristiane B.; Tanajura, Diego M.; Silva, Angela M.; Lipscomb, Michael W.; Borges, Valéria M.; Jesus, Amélia R.; Almeida, Roque P.; de Moura, Tatiana R. (Frontiers in Microbiology, 2017)
Visceral leishmaniasis (VL) is a systemic transmissible disease that remains to be a major global health problem. The inflammatory response during VL is characterized by the release of several cytokines and other pro-inflammatory mediators. Triggering Receptor Expressed on Myeloid Cells (TREM) are a group of evolutionarily conserved membrane-bound surface receptors expressed on neutrophils and monocytes. Engagement of TREM-1 directs intracellular signaling events that drive cytokine production, degranulation, and phagocytosis. In certain inflammatory-associated diseases, TREM-1 can also be found as a soluble form (sTREM-1), which can negatively regulate TREM-1 receptor signaling. In these studies, we now find that high levels of circulating sTREM-1 correlate directly with VL disease severity. In particular, high levels of sTREM-1 were observed in non-survivor VL patients. Furthermore, these levels of sTREM-1 positively correlated with liver size and negatively correlated with leukocyte counts and hemoglobin concentration. Moreover, we found that neutrophils exposure in vitro to Leishmania infantum modulates TREM-1, DAP12, and IL-8 gene expression, while also increasing release of sTREM-1. Finally, results revealed that higher sTREM-1 levels are associated with increasing parasite ratio. Taken together, these studies suggest that Leishmania infantum may modulate TREM-1 in neutrophils and high levels of this molecule is associated with severe VL.